Vestibular Evoked Myogenic Potentials and Postural Control in Adults with Age-Related Hearing Loss - Doettl, Steven M.; Plyler, Patrick N.; McCaslin, Devin L.; Conolly, Larissa G.; Gomez, Jesus D. (Journal of the American Academy of Audiology, 2021)
Background Age-related changes to auditory function have been attributed to, through histopathological study, specific degradation of the sensory, supporting, and afferent structures of the cochlea. Similar to age-related hearing loss (ARHL), age-related changes to the vestibular sensory and supporting structures with specific degeneration of the saccule, utricle, otoconia, primary vestibular afferents have also been noted. Significant decreases in postural control with age are also well-documented in the literature attributed to multifactorial changes in function.Purpose The purpose of this study is to further evaluate the association of ARHL and saccule/utricle function as measured by VEMPs and postural control measures.Study Sample Audiologic, vestibular and postural control results from 34 participants were analyzed. The age range was from 50 to 70 years old with 16 males and 18 females. Group 1 consisted of 33 ears from participants age 50–70 with normal hearing with average age of 60.8 years (sd 6.287 years) and an average speech-frequency PTA of 14.8 dB HL. Group 2 consisted of 27 ears from participants age 50–70 years with ARHL and an average age of 62.9 years (sd 4.984 years) with an average speech-frequency PTA of 39.9 dB HL.Data Collection and Analysis Independent samples t-tests were used to assess group mean differences for dependent variables. The independent variable was group with 2 levels (normal hearing, ARHL). The dependent variables were cVEMP P1/N1 Amplitude, cVEMP P1 Latency, cVEMP N1 Latency, cVEMP P2 Latency, oVEMP N1/P1 Amplitude, oVEMP N1 Latency, and oVEMP P1 Latency. Additional analyses were completed using Pearson correlation to evaluate the relationship of audiometric findings to the dependent variables.Results Results indicated significantly decreased cVEMP P1/N1 amplitude and oVEMP N1/P1 amplitude adults 50–70-years of age with ARHL compared with their normal counterparts. Significant correlations were also found for audiometric results and both cVEMP and oVEMP measures.Conclusions Overall, the results of this study describe concomitant auditory and vestibular degeneration as measured by audiometric testing and vestibular function testing involving the saccule and to a lesser degree the utricle.
Keywords: oVEMPS; cVEMPS; age related hearing loss; presbycusis; vestibular testing